Effectiveness of gathering activities and spaces for community recovery in GEJET-2011-affected areas - Yegane Ghezelloo; Akihiko Hokugo (Journal of Asian Architecture and Building Engineering, 2023)
Natural disasters are becoming more frequent around the world; as a result, more citizens are losing their homes, and community bonds are becoming weaker. To address this issue, scholars have emphasized the importance of providing diverse gathering spaces and activities within shelters, temporary housing sites, and permanent housing areas, to help rebuild communities. Providing such services helps to strengthen social bonds between different genders and groups, and it can facilitate the recovery of both the built environment and community cohesion. During the Great East Japan Earthquake and Tsunami 2011, many communities lost their settlements and were forced to relocate to new areas or reconstruct the old ones. Based on a series of site visits, interviews, and questionnaire surveys conducted for selected case studies, this study aims to determine the effectiveness of gathering spaces and recovery activities on the rebuilding of communities at different stages after the disaster. Different factors (e.g., gender and dwelling type) are found to be potentially effective at improving the benefits of such services; however, an inclusive approach providing diversified gathering spaces and activities is found to best help reduce bias between the beneficiaries and residents of gathering services and restore the community after a disaster.